Treatment Paradigms for Patients with Metastatic Non-Small Cell Lung Cancer, Squamous Lung Cancer: First, Second, and Third-Line - Al-Farsi, Abdulaziz; Ellis, Peter Michael (Frontiers in Oncology, 2014)
Historically, the treatment algorithm applied to non small cell lung cancer (NSCLC) was the same for all histologic subtypes. However, recent advances in our understanding of the molecular profiles of squamous and non-squamous NSCLC have changed this perspective. Histologic subtype and the presence of specific molecular abnormalities have predictive value for response to and toxicity from therapy, as well as overall survival. For patients with squamous NSCLC, a platinum agent plus gemcitabine, or paclitaxel is recommended as first-line therapy. The role of EGFR monoclonal antibodies is uncertain. Maintenance therapy is not widely recommended, although data exist for the use of erlotinib. The standard recommendation for second-line therapy is docetaxel and erlotinib should be considered as second or third-line therapy. There is ongoing research identifying molecular targets in squamous NSCLC and many agents are in early phase clinical trials. Immunotherapeutic approaches targeting programmed death 1 receptor (PD-1) and its ligand (PD-L1) appear promising.